Athletic hand injuries in intercollegiate field hockey players - Bowers, A. L.; Baldwin, K. D.; Sennett, B. J. (Medicine & Science in Sports & Exercise, 2008)
Purpose: Protective gloves are worn for stick-handling sports, including ice hockey, men's lacrosse, and women's lacrosse, but are not mandated for women's field hockey. The purpose of this study is to evaluate whether collegiate field hockey players are at increased risk for significant hand injuries compared with stick-handling athletes who wear protective gloves.